Catalyzing Ethical Business Practices: Exploring the Role of Islamic Finance in Contemporary Markets - Harti, Sugi (International Journal of Business, Law, and Education, 2024)
This research explores the role of Islamic finance in catalyzing ethical business practices within contemporary markets. Through quantitative analysis, the study examines the relationships between familiarity with Islamic finance, implementation of its principles, organizational characteristics, and the importance of ethical behavior and engagement in corporate social responsibility (CSR) activities. The results reveal significant positive correlations between familiarity with Islamic finance and ethical behavior, as well as between implementation of Islamic finance principles and CSR engagement. Moreover, organizational characteristics also play a role in influencing ethical decision-making processes. These findings highlight the potential of Islamic finance to promote ethical conduct and CSR initiatives, contributing to a more sustainable and socially responsible business landscape.